The Effect of Financial Literacy and Digital Payment Services on the Financial Performance of MSMEs - Ika Atikah; Yuniatin Trisnawati Dwi Kusuma Wardani (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2025)
The purpose of this research is to examine the influence of financial literacy and digital payment services on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the dry and wet cake industry in the Surakarta region. This research uses a quantitative approach and data were collected using questionnaires. The population in this study was MSMEs registered on the website umkm.surakarta.go.id in the dry cake and wet cake industry, with the sampling technique useds purposive sampling. The analysis technique uses multiple linear regression. The research results show that financial literacy partially has a positive and significant effect on the financial performance of MSMEs, while digital payment services partially have a negative and insignificant effect on the financial performance of MSMEs. Simultaneously, financial literacy and digital payment services have a positive and significant effect on the financial performance of MSMEs.